2015
DOI: 10.1105/tpc.114.134338
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Biochemical Basis of Temperature-Induced Lipid Pathway Adjustments in Plants

Abstract: Glycerolipid biosynthesis in plants proceeds through two major pathways compartmentalized in the chloroplast and the endoplasmic reticulum (ER). The involvement of glycerolipid pathway interactions in modulating membrane desaturation under temperature stress has been suggested but not fully explored. We profiled glycerolipid changes as well as transcript dynamics under suboptimal temperature conditions in three plant species that are distinctively different in the mode of lipid pathway interactions. In Arabido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
196
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(207 citation statements)
references
References 81 publications
7
196
2
2
Order By: Relevance
“…The PUFA content of Arabidopsis leaf lipids also responds to temperature (Falcone et al, 2004). However, the change reported in leaf PC composition between 10°C and 30°C is very modest (Li et al, 2015) compared with our data in seeds. Sanyal and Linder (2013) also reported that there is no significant relationship between the temperature response of fatty acid composition in seed TAG and leaf phospholipids across 84 Arabidopsis accessions.…”
Section: Positioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The PUFA content of Arabidopsis leaf lipids also responds to temperature (Falcone et al, 2004). However, the change reported in leaf PC composition between 10°C and 30°C is very modest (Li et al, 2015) compared with our data in seeds. Sanyal and Linder (2013) also reported that there is no significant relationship between the temperature response of fatty acid composition in seed TAG and leaf phospholipids across 84 Arabidopsis accessions.…”
Section: Positioncontrasting
confidence: 69%
“…Temperature can influence the degree of microsomal fatty acid desaturation indirectly through its effects on substrate availability (Harris and James, 1969;Browse and Slack, 1983;Rolletschek et al, 2007;Li et al, 2015). However, there also is evidence that FAD2 and FAD3 are regulated directly by temperature (Tang et al, 2005;O'Quin et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4,42] The mechanism underlying these lipid trafficking processes is not fully understood. [3,4,43] In Arabidopsis and Atriplexlen tiformis, low temperatures up-regulate the chloroplast pathway and channel glycerolipids from the ER to the chloroplast, whereas high temperatures increase the contribution of the eukaryotic pathway but suppress the prokaryotic pathway. [43] Arabidopsis ABC lipid transporters are believed to be involved in the ER-chloroplast phospholipid trafficking consisting of TGD1, 2, and 3, which are located in the inner membrane envelope (Figure 2).…”
Section: Er-plastid Phospholipid and Fa Transportmentioning
confidence: 99%
“…The regulation of glycerolipid pathways also is induced in Arabidopsis, wheat (Triticum aestivum), and saltbush (Atriplex spp.) in response to temperature stress, which results in diacylglycerol trafficking from the endoplasmic reticulum to the chloroplasts (Li et al, 2015). In Arabidopsis, heat, salt, and drought also induce triacylglycerol accumulation in the cytosol, an adaptation that enables structural remodeling of membrane lipids (Mueller et al, 2015).…”
Section: Importance Of Glycerol and Energy Metabolism As Safety Valvesmentioning
confidence: 99%